The Effect of Two-Month Administration of Methylphenidate on Appetite, Olfaction and Energy Intake in Individuals with Obesity - El Amine, Fatme (Université d'Ottawa / University of Ottawa, 2019)
Background: Dopamine levels has been implicated in obesity, feeding behaviour, and hedonic control of appetite like olfactory cues and food palatability. Methylphenidate (MPH) is a dopamine reuptake inhibitor that increases brain dopamine levels and has been shown to reduce appetite and promote weight loss in patients with attention deficit hyperactivity disorder (ADHD). As such, the objectives of this study were to test the possible effect of MPH on appetite, olfaction, and food palatability as well as its effects on energy intake and body weight of healthy individuals with obesity. Methods: In a randomized, double-blind study, 12 participants (age 28.9±6.7 yrs) (BMI 36.1±4.5 kg/m2) were assigned to receive MPH (0.5mg/kg) (n=5) or placebo (n=7) twice daily for two months. Appetite and palatability (Visual Analog Scale (VAS)), odour threshold (Sniffin’ Sticks®), in-lab energy intake (ad libitum buffet), free-living energy intake (3-day food boxes) and body weight (DEXA scan) were measured at baseline (day 1) and final visit (day 60). Results: MPH intake caused significantly greater suppression of appetite sensations (desire to eat (p=0.001), hunger (p=0.008), and prospective food consumption (p=0.003)) and increase in fullness (p=0.028) over time compared to placebo. There was a significant increase in odour threshold scores in the MPH group (6.3±1.4 vs. 9.4±2.1) compared to placebo (7.9±2.3 vs. 7.8±1.9) (p=0.029). Both placebo and MPH groups showed decreases in their energy intake (p=0.021) and body weight (p=0.005) over time but with large effect sizes favouring greater reduction in the MPH group compared to placebo. Conclusions: Compared to placebo, MPH intake over 60 days suppressed appetite and improved olfactory sensitivity in individuals with obesity. These data provide novel findings into the possible efficacy of MPH to favourably impact appetite and therefore promoting weight loss in individuals living with obesity.
Keywords: Methylphenidate; dopamine; food reward; feeding behaviour; obesity pharmacotherapy; weight loss; food palatability; olfaction; appetite